Nusyuz's Analysis in the Perspec Analisis Nusyuz dalam Perspektif Kompilasi Hukum Islam (KHI) dan Relevansinya dengan UU No. 23 Tahun 2004 (Penghapusan Kekerasan dalam Rumah Tangga (KDRT)): Nusyuz - Miftakhul Mukharrom Miftah (El 'Ailaah, 2023)
Abstract : Nusyuz is an attitude of disobedience by a wife against her husband and does not fulfill its obligations as a wife in the family. In the Qur'an, it has been explained unequivocally that when a wife does nusyuz, she should be addressed by providing advice, separating beds and hitting without injuring. In carrying out these stages, sometimes a lot of people do not understand; then this is where the need to understand what the real intention of nusyuz according to the implemented Islamic Law Compilation in Indonesia. This study was a library research; so that type of the needed data was entirely qualitative data which are obtained from various written sources (classical and contemporary) that talk about the investigated problem. Data analysis technique was the content analysis or descriptive analysis. Descriptive, as this study starts from the concepts based on the texts of syara’ (law), the opinion of jurists and regulations that exist as a norm of positive law (tasyri'iyyah). The data were classified into three types of data, namely primary data source as the basic source that included chapters of KHI (Islamic Law Compilation), Law No. 23 of 2004, and books directly related on nusyuz and domestic violence. The secondary data source was as the supporting source obtained from various sources, such as the books of fiqh like al-Um, Bidayah al-Mujtahid, Fathulmuin, etc. While the tertiary data sources were obtained from journals, newspapers, internet, dictionary and related data on the topic of discussion. The conclusions of the discussed issues are, first, to understand the concept nusyuz in KHI we have to go back to fiqh books as a translation of the KHI’s articles. Second, to deal with a wife who is nusyuz, Islam does not legalize the Muslims to commit domestic violence (physical or psychological), even abandoned, but Islam set it very wisely as a way to solve nusyuz. Third, the relevance between nusyuz in KHI and Law No. 23 of 2004 is especially relevant when it can be understood and implemented properly, if not, then there will be abuse of the wife because she felt being very protected by the state, although it is wrong in the religious perspective.